Oncology in Mozambique: Overview of the Diagnostic, Treatment, and Research Capacity - Tulsidás, S (2023)
Simple Summary Mozambique is one of the poorest countries in the world. Because of the limited number of human and material resources, priority is usually given to infectious diseases because they are the main cause of death in Mozambique. However, with the increasing adoption of an unhealthy lifestyle, the number of deaths attributed to cancer is also increasing. This review summarizes cancer incidence and mortality, cancer prevention and screening, cancer care resources, and trends in cancer training and research in Mozambique, providing a background for the development of cancer care policies in the country. Mozambique is one of the poorest countries worldwide, with nearly two thirds of the population living below the poverty line. Similarly to other less developed countries, there is a weak provision of health care for non-communicable diseases due to competing priorities with infectious diseases. Although the leading causes of death in Mozambique in 2019 were Acquired Immune Deficiency Syndrome/Human Immunodeficiency Virus and other sexually transmitted diseases and respiratory infections and tuberculosis, with increasing urbanization and westernization of lifestyles, deaths attributed to cancer are also on the rise. This review summarizes cancer burden, cancer prevention and screening, cancer care resources, and trends in cancer training and research in Mozambique, providing a background for the development of cancer care policies in the country.